Pengaruh Kemampuan Awal dan Minat Belajar terhadap Prestasi Belajar Fisika - Siwi Puji Astuti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2015)
The study objective was to determine the effect of the prior knowledge and interest in learning to learn Physics achievement. The method used in this study is a survey method. Analysis using multiple regression and correlation techniques. Sample size of 76 students obtained by Slovin technique. The instrument used was a multiple choice test to measure the prior knowledge and questionnaire to measure the interest in learning, while performance is taken from the document teacher learning. Results of the hypothesis test, namely (1) there is the influence of prior knowledge and interest in learning together toward physics learning outcomes (2) there is the influence of prior knowledge on learning outcomes of pyhsics (3) there is the influence of interest in learning on learning outcomes of pyhsics